Toleransi Beragama: Studi Komparatif Antar Perguruan Tinggi Keagamaan di Wilayah Indonesia Tengah - Manuain, Leryani Mince Maria; Thoomaszen, Friandry Windisani; Sheldena, Devi Novita; Mila, Suryaningsi; Hilli, Yandri (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2024)
This study aims to identify the level of religious tolerance in public religious universities in Indonesia, especially in the Central Indonesia region, and to understand the factors that influence students' tolerant attitudes. A mixed methods approach was used in this study, which involved collecting quantitative data through a Likert-scale questionnaire and qualitative data through Focus Group Discussions (FGDs) in several Islamic, Christian, and Hindu faith-based universities. Quantitative data were analyzed using quantitative descriptive statistical tests, while qualitative data were analyzed using interpretative phenomenological analysis (IPA) to explore students' experiences in implementing religious tolerance.The results showed that the level of religious tolerance in state religious universities tends to be stable, with the dimension of reasonableness (ability to think logically) showing the highest value, followed by the dimensions of empathy and fairness. Female students tend to have higher tolerance potential, and the experience of interacting with people of other religions has a significant effect on increasing tolerance. However, the lack of space for interfaith encounters in the campus environment is an obstacle to the real application of the concept of tolerance.